The competitive relationship between cloud computing and generative AI - Christophe Carugati (Bruegel, 2023)
Cloud computing providers and generative artfi cial intelligence (GenAI) providers nurture a close, interdependent relationship: GenAI providers need cloud providers to train, run and deploy their GenAI solutions, while cloud providers see GenAI providers as a business driver to grow their market shares in cloud and related markets, such as productivity software or search engines. Th e cloud/GenAI relationship takes various forms, including exclusive and strategic partnerships, especially between large cloud providers and GenAI providers across all parts of the cloud market, including infrastructure, platforms and software. Competition benefi ts and risks are likely to result from the relationships. Competition benefi ts arise from increased competition and innovation in the cloud and GenAI sectors. Risks relate to potential concentrations arising from the partnerships between cloud and GenAI providers, and from anticompetitive practices, including discrimination in the supply of IT equipment by dominant IT providers, interoperability obstacles to switching, use of business-user data, self-preferencing of cloud services over third parties, tying and pure bundling. Merger control and antitrust laws can address some of the competition risks, while laws, including the European Union's Digital Markets Act and Data Act, can deal with competition issues in digital markets and the cloud sector. Nevertheless there are gaps. Th e European Commission should amend existing EU instruments, including by changing the defi nition of a concentration under merger control, and should specify interoperability requirements for cloud providers under the Data Act. The Commission should also closely monitor developments in and outside Europe through market investigations, including with international counterparts, and should intervene to tackle imminent competition risks using fast procedural tools, such as interim measures.
Keywords: 330